Building Resilient Healthcare Systems: Integrating Health Administration, Public Health, Nursing, Sociology, and Pharmacy - Suleiman Ghazi Alshammari,; Mousa Muhammad Mousa Fadel,; Hessah Hamood Fayad Alshammary,; Awad Suliman Alatawi,; Fahad Naji F. Alhaqbani,; Mohammed Dakheel Almutairi,; Monerah Hamad Alshathri, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Only by combining health administration, public health, nursing, sociology, and pharmacy can resilient healthcare systems be built. This paper delves into the role these fields play in building resilience in healthcare, especially during crisis times like the COVID-19 pandemic. Health administration focuses on governance, resource management, and policy-making to make healthcare organizations prepared for emergencies. Public health adds value through the prevention of diseases, early detection, and health monitoring. Nursing provides continuity of care delivery and communication during a crisis. It is sociology that helps build the understanding of the social determinants of health and community resilience. Pharmacy provides access to necessary medications and vaccines. It is the interaction of these disciplines that makes it possible for healthcare systems to respond and recover from health emergencies. Challenges and strategies for improvement across these fields are also discussed.